2017
DOI: 10.1111/1471-0528.14841
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prepregnancy obesity and the risk of shoulder dystocia: a meta‐analysis

Abstract: A meta-analysis shows that maternal prepregnancy obesity increases the risk of shoulder dystocia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 48 publications
3
25
0
4
Order By: Relevance
“…Maternal overweight and obesity is a public health challenge and contributes to adverse health outcomes for both mother [1,2] and infant [3][4][5]. During the past decade, there has been a greater increase in average body mass index (BMI) among women in Southeast Asia (>1 kg/m 2 ) than those residing in higher-income Asian countries (<0.2 kg/m 2 ) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal overweight and obesity is a public health challenge and contributes to adverse health outcomes for both mother [1,2] and infant [3][4][5]. During the past decade, there has been a greater increase in average body mass index (BMI) among women in Southeast Asia (>1 kg/m 2 ) than those residing in higher-income Asian countries (<0.2 kg/m 2 ) [6].…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the recently published online article by Zhang et al This meta‐analysis was performed to assess the risk of shoulder dystocia in women with prepregnancy obesity, in comparison with women who were not obese. The study found that obesity with a body mass index (BMI) of >30 kg/m 2 significantly increased the risk of shoulder dystocia in the pooled analysis.…”
mentioning
confidence: 99%
“…Meta-analyses and systematic reviews underline the fact that both women who are overweight and those who are underweight before conception have a higher health risk than those with normal weight 16 , 17 , 18 , 19 , 20 . The recommendation that women should adjust their body weight before pregnancy to that approaching a more normal weight is consistent with international 4 and national recommendations 21 , 22 .…”
Section: Body Weight Before Conception and Weight Gain In Pregnancymentioning
confidence: 99%